2016
DOI: 10.1159/000445665
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Signaling Pathway Changes with Intestinal Epithelial Cells Renewal Along Crypt-Villus Axis

Abstract: Background/Aims: Understanding the mechanism that involves in regulating epithelial cells renewal is the fundamental of regulating intestinal mucosa development and functions and related diseases. The mechanistic target of rapamycin (mTOR) signaling pathway involves in controlling various major processes by integrating intracellular and extracellular cues. The present experiment was conducted to test the correlation between the mTOR signaling pathway and intestinal epithelial cells renewal along crypt-villus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This ensures intestinal function and recovery from tissue damage (Fan et al, 2001;Yang et al, 2013a;Yang et al, 2016a). Intestinal epithelial cell renewal along the CVA is regulated by mechanistic targeting of rapamycin (mTOR), Wnt/β-catenin signaling pathways, and antioxidant capacity (Yang et al, 2013(Yang et al, , 2016b. Weaning stress in piglets usually disrupts intestinal epithelial cell renewal along the CVA and related signaling pathways and can result in morphological intestinal atrophy and dysfunction (Jiang et al, 2000;Yang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…This ensures intestinal function and recovery from tissue damage (Fan et al, 2001;Yang et al, 2013a;Yang et al, 2016a). Intestinal epithelial cell renewal along the CVA is regulated by mechanistic targeting of rapamycin (mTOR), Wnt/β-catenin signaling pathways, and antioxidant capacity (Yang et al, 2013(Yang et al, , 2016b. Weaning stress in piglets usually disrupts intestinal epithelial cell renewal along the CVA and related signaling pathways and can result in morphological intestinal atrophy and dysfunction (Jiang et al, 2000;Yang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level the mTOR (mechanistic target of rapamycin) pathway, which has been shown to be central to the maintenance of the crypt-villous axis, is regulated in FDR in a way that promotes the formation of villi. The mTOR C1 and c myc - APC pathways have been shown to be essential in regulation of the crypt-villous architecture 18 , 19 . These studies also show that the mTOR C1 pathway is progressively downregulated from the crypt to the villous and that this may be involved in regulating epithelial cell renewal along the crypt-villous axis.…”
Section: Discussionmentioning
confidence: 99%
“…Several recently published research articles revealed the impacts of weaning stress on the expression of proteins and metabolites in enterocytes of piglets (15)(16)(17)(18)(19)(20). Weaning significantly down-regulated the expression of proteins involved in the tricarboxylic acid cycle, β-oxidation, and the glycolysis pathway in the upper villus and middle villus of the jejunum in early-weaned pigs, but up-regulated proteins involved in glycolysis in crypt cells (15).…”
Section: Weaning Stress On Pig Intestinal Physiologymentioning
confidence: 99%